Magnesium intoxication in women with preeclampsia with severe features treated with magnesium sulfate - Muhammad Ilham Aldika Akbar; Daniel Yoseph; Aditiawarman -; Muhammad Adrianes Bachnas; Erry Gumilar Dachlan; Gustaaf Albert Dekker; Ernawati (Taylor & Francis Group, 2020)
Objective To evaluate the maternal-neonatal outcome in magnesium (Mg)-intoxicated women with preeclampsia with severe features (PESF) treated with magnesium sulfate (MgSO4). Methods A total of 19 Mg intoxicated PESF women (cases) were compared with 166 PESF women without signs of intoxication (controls). Results Mg serum levels of cases was higher compared to control group (12.36 ± 3.54 mg/dl versus 2.69 ± 0.83 mg/dl). 3 women died and 3 had major maternal morbidity in cases group compared with zero in the control group (P = 0.009). Mg intoxication was also significantly associated with perinatal deaths and low Apgar scores at 1 and 5 minutes. Conclusion Mg intoxication is associated with a increased risk of maternal and perinatal mortality and morbidity.